2020
DOI: 10.3389/fcell.2020.602278
|View full text |Cite
|
Sign up to set email alerts
|

Blood Vessels and Vascular Niches in Bone Development and Physiological Remodeling

Abstract: Recent advances in our understanding of blood vessels and vascular niches in bone convey their critical importance in regulating bone development and physiology. The contribution of blood vessels in bone functions and remodeling has recently gained enormous interest because of their therapeutic potential. The mammalian skeletal system performs multiple functions in the body to regulate growth, homeostasis and metabolism. Blood vessels provide support to various cell types in bone and maintain functional niches… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 129 publications
(286 reference statements)
0
39
0
Order By: Relevance
“…In addition, a time-dependent interplay between IAld and I3AA concomitant treatment was observed. These findings highlight the potentially differential outcomes in arthritic severity depending on the relative levels of these two indole-derivates by acting at different stages of blood vessel formation [ 54 ]. Additionally, we observed that CH-223191 failed to suppress the pro-angiogenic effect of IAld but the anti-angiogenic effect of I3AA was reversed by CH-223191.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a time-dependent interplay between IAld and I3AA concomitant treatment was observed. These findings highlight the potentially differential outcomes in arthritic severity depending on the relative levels of these two indole-derivates by acting at different stages of blood vessel formation [ 54 ]. Additionally, we observed that CH-223191 failed to suppress the pro-angiogenic effect of IAld but the anti-angiogenic effect of I3AA was reversed by CH-223191.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of bone vasculature, large blood vessels enter through the cortex mid‐shaft in larger bones, branching toward the metaphyses and along endosteum, where type H capillaries are found, and into the marrow, which holds a highly branched sinusoidal network of type L vessels. ( 66 ) Oxygen levels are higher in the areas fed by type H vessels than type L, and the endothelium of these vessels differs as well. The differing oxygenation of these microenvironments may dictate localization and proliferation of pathogens with different tolerance of oxygen (ie, facultative versus strict anaerobic bacteria), but this has not been directly tested yet.…”
Section: Local/regional Bone Factorsmentioning
confidence: 96%
“…Finally, the organization of blood vessels and nerve fibers, which often run together, at least through cortical bone, varies substantially both within and across bones. ( 66–69 ) In addition to providing openings in the bone matrix through which microbes can travel, both neural and vascular cells can interact with host and pathogen. In terms of bone vasculature, large blood vessels enter through the cortex mid‐shaft in larger bones, branching toward the metaphyses and along endosteum, where type H capillaries are found, and into the marrow, which holds a highly branched sinusoidal network of type L vessels.…”
Section: Local/regional Bone Factorsmentioning
confidence: 99%
“…The skeleton is a highly vascularized tissue containing an abundant capillary network, which not only provides access to nutrients and oxygen, but also secretes various cytokines, regulating the local osteogenic microenvironment (Stegen et al, 2015;Ramasamy et al, 2016;Hendriks and Ramasamy, 2020;Stucker et al, 2020). Kusumbe defined type-H endothelial cells, which exhibit important functions in the regulation of osteogenesis and angiogenesis, based on the criterion of a high expression of platelet endothelial cell adhesion molecule-1 and endomucin (CD31 hi EMCN hi ) (Kusumbe et al, 2014).…”
Section: Introductionmentioning
confidence: 99%